2016
DOI: 10.7567/apex.9.045801
|View full text |Cite
|
Sign up to set email alerts
|

Complementary resistive switching of annealed Ti/Cu2O/Ti stacks

Abstract: Ti/Cu2O/Ti stacks with 25-nm-thick Cu2O layers were produced by sputter deposition and lift-off processes utilizing three photolithographic masks. Subsequent annealing of the Ti/Cu2O/Ti stacks at 250 °C in a vacuum induced interfacial reactions between the Ti and Cu2O layers and converted the Ti/Cu2O/Ti stacks to a Ti/TiO x /Cu/TiO x /Ti structure. This pentalayered stack resembled a pair of antiserial Ti/TiO x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In another approach, complementary resistive switching (CRS) can reduce the sneak leakage paths through a large array. The conceptual design, as proposed by Linn et al, is based on three metal lines, i.e., back‐to‐back connection of two adjacent RRAM cells . Therefore, if two cells maintain low resistance state (LRS) then the total resistance of the devices is in LRS, but if one of them is in high resistance state (HRS) then the total resistance is HRS.…”
Section: Introductionmentioning
confidence: 99%
“…In another approach, complementary resistive switching (CRS) can reduce the sneak leakage paths through a large array. The conceptual design, as proposed by Linn et al, is based on three metal lines, i.e., back‐to‐back connection of two adjacent RRAM cells . Therefore, if two cells maintain low resistance state (LRS) then the total resistance of the devices is in LRS, but if one of them is in high resistance state (HRS) then the total resistance is HRS.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al reported a CRS device consisting of two symmetric memory cells based on Ti/TiO x /Cu/TiO x /Ti structure, as shown in Figure 7b. [ 154 ] Other reports of symmetrically connected pair of memory cells have been demonstrated, like Pt/BTO/LSMO/BTO/Pt, [ 155 ] Au/a‐C/CNT/a‐C/Au, [ 156 ] Pt/TiO x /TiO y /TiO x /Pt. [ 157 ] 2) CRS using two asymmetric memory cells.…”
Section: Solutions To the Sneak‐path Current Problem In Crossbar Arraysmentioning
confidence: 99%
“…Reproduced with permission. [ 154 ] Copyright 2016, IOP Publishing. The left top inset shows the schematic of the CRS device and the right lower inset shows the endurance performance of the CRS device at 0.5 V. c) A simple scheme of heterodevice CRS device having these two RRAMs and simple illustrations of device states.…”
Section: Solutions To the Sneak‐path Current Problem In Crossbar Arraysmentioning
confidence: 99%
“…9) Our previous studies also demonstrated RS of metal oxide-based RRAM, such as Cu/Cu-SiO 2 /Al, 10) Cu/Cu-TaO x /TaN, 11) AZO/SiO x /ITO, 12) and Al/AlO x -CuO x /Al-Cu, 13) and complementary RS of annealed Ti/Cu 2 O/Ti stacks. 14) The Cu/Cu-TaO x /TaN device could demonstrate two LRSs. 11) Recently, metal sulfides have been employed for RRAM, such as Ag/MoS 2 /Pt, 15) Ti/MoS 2 /Pt, 15) and Al/WS 2 /Pt.…”
Section: Introductionmentioning
confidence: 99%